Sal Mortality in Bihar - Seth, S. K.; Khan, M. A. Waheed; Yadav, L. S. P. (Indian Forester, 1960)
Wide-spread sal (Shorea robusta) mortality occurred in the Forest Divisions of Daltongunj, Latehar and Ko1han in Bihar in 1951 onwards. Drought was suspected to be the main cause of this calamity and accordingly a study of climate was undertaken and monthly fluctuations of soil moisture in the entire profiles of 6 ft. depth at three locations were computed for the period from 1941 to 1955. These values of soil moisture were grouped into five categories and taking into consideration the periods during which each of these moisture conditions prevailed in the root zones ’drought values’ and ’drought severity values’ were determined as percentage departures from the normal conditions of duration and moisture status. These values were integrated to arrive at ’drought mortality values’ and the effect of successive drought years was assessed as ’cumulative drought mortality values’ (C.D.M.V.). The observed pattern of mortality was correlated with these values. The close correlation between the cumulative drought mortality values and the actual pattern of mortality at Daltongunj proves that drought is the main cause of mortality. Management of such drought-affected sal forests is also suggested.